ICT Update 72: Opening access and open data - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2013)
ICT Update is a bimonthly printed and on line magazine (http://ictupdate.cta.int) and an accompanying email newsletter published by CTA. This issue focuses on open access strategies and open data initiatives.